Unprecedented high insulin secretion in a healthy human subject after intravenous glucagon-like peptide-1: a case report - Knop, Filip K (BioMed Central, 2014)
BACKGROUND: The gut-derived incretin hormones, glucose-dependent insulinotropic polypeptide and glucagon-like peptide-1, are released in response to ingestion of nutrients. Both hormones are highly insulinotropic in strictly glucose-dependent fashions and glucagon-like peptide-1 is often referred to as one of the most insulinotropic substances known. CASE PRESENTATION: Plasma insulin and C-peptide concentrations were measured in a healthy Caucasian male (age: 53 years; body mass index: 28.6 kg/m(2); fasting plasma glucose: 5.7 mM; 2 h plasma glucose value following 75 g-oral glucose tolerance test: 3.5 mM; glycated haemoglobin A(1c): 5.5%) during glucagon (1 mg) and meal (2,370 kJ) tests, and during two 2 h 15 mM-hyperglycaemic clamps with continuous intravenous infusion of glucagon-like peptide-1 (1 pmol/kg/min) and glucose-dependent insulinotropic polypeptide (4 pmol/kg/min), respectively. Normal insulin and C-peptide responses were observed during meal test (peak concentrations: 300 and 3,278 pM) and glucagon test (peak concentrations: 250 and 2,483 pM). During the hyperglycaemic clamp with continuous intravenous infusion of GLP-1 the subject exhibited plasma insulin and C-peptide concentrations of 13,770 and 22,380 pM, respectively. CONCLUSIONS: To our knowledge insulin and C-peptide concentrations of these magnitudes have never been reported. Thus, the present data support the view that glucagon-like peptide-1 is one of the most insulinotropic substances known.